Striding towards sustainability: A framework to overcome challenges and explore opportunities through industry 4.0 - Reis, José Salvador da Motta [UNESP]; Espuny, Maximilian [UNESP]; Nunhes, Thaís Vieira [UNESP]; Sampaio, Nilo Antonio de Souza; Isaksson, Raine; de Campos, Fernando Celso; de Oliveira, Otávio José [UNESP] (MDPI, 2021)
Sustainability 4.0 (S4.0) enables sustainable development through intelligent technologies to meet economic, environmental and social demands. The main objective of this article is to propose a framework for developing S4.0 in sectors of Triple Helix (TH) (Government, Organizations and Academy). The framework consists of benchmarking of policies and initiatives from the Science‐ Technology Scenario in S4.0 (STS‐S4.0) and the authorʹs experience. The STS‐4.0 is a snapshot of relevant initiatives from the countries that performed best in science and technology in S4.0. This work uses the methods of bibliometric studies and content analysis of scientific articles from the Scopus database and patents publications from the Orbit database. This research resulted in a total of 19 propositions for developing sustainability through I4.0. Of these, eight are for Government, six for Organizations and five for Academy. The main scientific contribution of this work is to expand and deepen the recent block of knowledge on S4.0. As for the applied contribution, this work contributes to the conscious and sustainable development of humanity through the technological elements of I4.0, contributing to the achievement of the following SDGs proposed by the UN: 9 (Industries, Innovation and Infrastructure), 11 (Sustainable Cities and Communities) and 13 (Climate Action). The main novelty of this article is the creation of paths for Government, Organizations and Academy to interactively lead the development of global sustainability through the smart technologies of I4.0.
Keywords: Industry 4.0; Intelligent technologies; Sustainability 4.0; Sustainable Development Goals; Triple Helix